The final year [videorecording (DVD)] - Obama, Barack; Kerry, John, 1943-; Power, Samantha; Rhodes, Ben, 1977- (Magnolia Home Entertainment, 2018)
A chronicle of the Barack Obama administration's foreign policy team and the events of Obama's final year in office.